SAPERE AUDE DAN ECHO CHAMBER: KEBERANIAN BERPIKIR KANT DI ERA DIGITAL - Albertus Brianto Kako; Agustinus Deni Lewar; Emilianus Julio Namput; Fridolin Anus Abu; Wilibrodus Elu; Aprianus Jandu (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) - Universitas Muhammadiyah Cirebon, 2026)
This article examines the phenomenon of the echo chamber in the digital era, which increasingly narrows the space for dialogue and weakens critical thinking due to social media algorithms that continuously reinforce users’ existing beliefs. This study aims to analyze the relevance of Immanuel Kant’s concept of sapere aude as a philosophical response to the echo chamber phenomenon and to propose a pathway toward intellectual freedom in the digital sphere. The research employs a qualitative method with a library research approach by examining Kant’s works and scholarly literature on echo chambers, digital media, education, and digital literacy. The findings reveal that echo chambers not only foster social polarization and the spread of misinformation but also threaten the autonomy of reason by limiting openness to diverse perspectives. In this context, Kant’s principle of sapere aude, stressing the bravery to think independently, remains highly relevant as a foundation for intellectual freedom. Education, digital literacy, cross-perspective dialogue, and the cultivation of critical thinking are essential means of reviving the spirit of enlightenment in the digital age. Therefore, Kant’s thought provides a strong philosophical foundation for developing an autonomous and critical culture of thinking capable of confronting the challenges posed by echo chambers in contemporary digital society.